Development Of Lab On Printed Circuit Board Based Heavy Metal Detection - Beh, Khi Khim (2023)
Heavy metal contamination in water sources is a significant environmental problem that poses a threat to public health. Electrochemical detection is a promising approach to detecting and quantifying heavy metals in water, due to the high sensitivity and selectivity it provides. However, traditional working electrodes, such as glassy carbon and mercury, are not ideal for detecting heavy metals due to limitations such as low sensitivity and toxicity. To address these limitations, this study aimed to improve the design and fabrication complexity of electro-analytical sensors by implementing a conventional Printed Circuit Board (PCB) fabrication technique. The fabricated sensor has achieved miniaturization of 40% compared to existing electrochemical sensors. According to cyclic voltammetry (CV) measurements, the fabricated sensor can produce a reversible peak reaction with different scan rates between 100 mV/s to 10 mV/s achieving a peak current ratio of 1. The modified Graphene Oxide (GO) of 0.2 mg/ml on the working electrode was explored as a sensing material due to its high sensitivity and selectivity in detecting heavy metals such as lead and cadmium, with an improvement of 45% in the detection of these metals. The optimum conditions for the detection of lead and cadmium were determined with a 10-minute accumulation time, -0.4 v reduction potential, 7-minute reduction time, and pH 4.0 of 0.1 M HCL buffer solution.